1989
DOI: 10.1111/j.1471-4159.1989.tb09143.x
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside Composition of Normal and Mutant Mouse Embryos

Abstract: The enrichment of gangliosides in neuronal membranes suggests that they play an important role in CNS development. We recently found a marked tetrasialoganglioside deficiency in twl/twl mutant mouse embryos at embryonic day (E)-11. The recessive twl/twl mutants die at embryonic ages E-9 to E-18 from failed neural differentiation in the ventral portion of the neural tube. In the present study, we examined the composition and distribution of gangliosides in twl/twl mutant mouse embryos at E-12. The total ganglio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 64 publications
3
33
0
Order By: Relevance
“…Bouvier and Seyfried (1989) observed that the predominant gangliosides in E12 mouse embryos were GD3 (51% of total sialic distribution), GM3 (19%), and GT1b (9.6%); other gangliosides occurred in much lower amounts (GM2 (2.6%), GM1 (1.6%), GD1a (3.7%), GD1b (6.3%), and GQ1b (4.5%)). Similar distributions were observed in both neural and non-neural embryonic structures, suggesting that undifferentiated embryonic cells in mice express GM3 and GD3 as the major ganglioside species (Bouvier and Seyfried, 1989). However, little is known about the expression of GT1b in preimplantation embryos.…”
Section: Gangliosides In Mouse Embryonic Developmentmentioning
confidence: 96%
See 3 more Smart Citations
“…Bouvier and Seyfried (1989) observed that the predominant gangliosides in E12 mouse embryos were GD3 (51% of total sialic distribution), GM3 (19%), and GT1b (9.6%); other gangliosides occurred in much lower amounts (GM2 (2.6%), GM1 (1.6%), GD1a (3.7%), GD1b (6.3%), and GQ1b (4.5%)). Similar distributions were observed in both neural and non-neural embryonic structures, suggesting that undifferentiated embryonic cells in mice express GM3 and GD3 as the major ganglioside species (Bouvier and Seyfried, 1989). However, little is known about the expression of GT1b in preimplantation embryos.…”
Section: Gangliosides In Mouse Embryonic Developmentmentioning
confidence: 96%
“…On E13, mST3GalV mRNA was expressed in various neural and non-neural tissues and in the telencephalon, while on E15, strong expression of mST3Gal V was observed in the liver (Ji et al, 2000). Bouvier and Seyfried (1989) observed that the predominant gangliosides in E12 mouse embryos were GD3 (51% of total sialic distribution), GM3 (19%), and GT1b (9.6%); other gangliosides occurred in much lower amounts (GM2 (2.6%), GM1 (1.6%), GD1a (3.7%), GD1b (6.3%), and GQ1b (4.5%)). Similar distributions were observed in both neural and non-neural embryonic structures, suggesting that undifferentiated embryonic cells in mice express GM3 and GD3 as the major ganglioside species (Bouvier and Seyfried, 1989).…”
Section: Gangliosides In Mouse Embryonic Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Flow cytometric analysis, enzyme assay, and product characterization showed that the enzyme catalyzes the formation of GD3 by the transfer of a sialic acid molecule from CMP-NeuAc to the terminal sialic acid of GM3 via an a2-8 linkage. A GD3 synthase is a key enzyme in the "b" metabolic pathway of gangliosides (GD3, GD1b, GT1b, and GQ1b) which are associated with neural cell differentiation (44)(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%